Evaluative Directions for the World Bank Group's Safeguards and Sustainability Policies - Dani, Anis; Freeman, Ade; Thomas, Vinod (Washington, DC: World Bank, 2012)
The financial and food crises are reminders of the growing challenges countries face in sustaining economic growth and lifting the living standards of the poor. Equally, the emerging impacts of global warming on natural disasters and on agriculture are warning signs of the urgency to care for the environment and society. Recent global experience in the financial and environmental arenas demonstrates clearly the need to put in place and enforce regulatory frameworks that balance costs and benefits, both private and social. In this context, the crucial questions in the recent evaluation by the Independent Evaluation Group (IEG) of the World Bank Group's safeguards and sustainability policy framework concern the effectiveness of the instrument in mitigating adverse environmental and social impacts of development programs, and suggesting ways to improve the results. IEG's evaluation covered projects approved from FY1999 to FY2008. During this period, social and environmental effects were significant in half of World Bank projects 1,402 with commitments of $109 billion; 88 percent of projects financed by the International Finance Corporation (IFC) 1,662 with commitments of $35 billion; and 217 guarantees by the Multilateral Investment Guarantee Agency (MIGA). The main thrust of the evaluation findings is that the World Bank Group's safeguards and sustainability policies have helped avoid or mitigate large-scale social and environmental risks in the projects it financed, but many projects with substantial environmental and social impacts remain of concern primarily because of inadequate supervision and follow-up.